Seizure burden in severe early‐life epilepsy: Perspectives from parents - Berg, Anne T. (Epilepsia Open, 2019)
OBJECTIVES: Seizure burden is typically measured by seizure frequency yet it entails more than seizure counts, especially for people with severe epilepsies and their caregivers. We aimed to characterize the multi‐faceted nature of seizure burden in young people and their parents who are living with severe early‐life epilepsies. METHODS: A one‐day workshop and a series of teleconferences were held with parents of children with severe, refractory epilepsy of early‐life origin and providers for children with epilepsy. The workshop sessions were structured as focus groups and aimed to identify components of seizure burden and their impact from the perspective of parents and providers. Data were gathered, organized, and refined during the workshop using an iterative 4‐step process that drew upon grounded theory. RESULTS: Three primary components of seizure burden were identified: frequency, severity, and unpredictability, which was as important if not more important at times than frequency and severity. Caregivers noted that the impacts of seizures were experienced as acute‐immediate consequences, longer‐term consequences, and as chronic effects that develop and evolve over time. The severity of the child's neurological and medical status as well as where in the disease journey a family was represented additional contextual factors that influenced the experience of seizure burden. SIGNIFICANCE: Patient‐reported and patient‐centered outcomes are increasingly incorporated into the evaluation of treatment effectiveness. Without understanding how the disease creates burden for the patient (or family), it is difficult to know how to assess the impact of treatment. Our preliminary findings indicate seizure burden is a complex construct and unpredictability can be as important as frequency and severity.